Rancang Bangun Sistem Informasi Pemesanan Makanan Berbasis Web pada Deshake Coffee - Darmawan, Rahmat; Marbun, Nasib (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to design and develop a web-based food ordering information system specifically tailored to the needs of the cafe, this research emphasizes the importance of technology adoption to improve customer experience. The system will allow customers to place orders online easily and conveniently through an intuitive user interface. In addition, the integration of a secure payment system, effective order management, and the availability of accurate product information are the main focuses in its development. In the context of Deshake Coffee, the system is designed to allow customers to place food orders easily from anywhere, through any internet-connected device. An intuitive user interface will guide users through the ordering process, while integration with a secure payment system will guarantee smooth and reliable transactions. Effective order management will help Deshake Coffee to manage orders more efficiently, minimize errors, and optimize product delivery to customers. In addition, the system will provide customers with accurate and up-to-date product information, ensuring that they always have the information they need to make informed purchasing decisions. By implementing this ordering information system, Deshake Coffee is expected to not only expand its market reach through an online platform, but also improve inventory management and overall order management. It is hoped that the results of this research can make a positive contribution to the development of technology in the food and beverage industry, as well as significantly increase Deshake Coffee's customer satisfaction.